Prosocial Behavior and Psyhcological Difficulties as Predictors of Depressive Symptomps in Adolescents: A Cross-Sectional Study - Yuliastuti, Estin; Istiqomah, Nurul (STIKep PPNI Jawa Barat, 2025)
Background: Adolescence is a crucial transitional period marked by significant changes and increased vulnerability to mental health problems, including depression. Objective: This study aimed to examine the relationship between prosocial behavior and psychological difficulties with depressive symptoms in adolescents. Methods: A quantitative correlational study with a cross-sectional approach was conducted among 155 adolescents aged 12–18 from a public senior high school in Surakarta, Indonesia. Data were collected using the Strengths and Difficulties Questionnaire (SDQ) and the Patient Health Questionnaire-9 (PHQ-9), and analyzed using Spearman’s correlation. Results: There was a strong positive correlation between psychological difficulties and depressive symptoms (r=0.656, p<0.001), while prosocial behavior was also significantly associated but with a weaker correlation (r=0.168, p=0.037). Conclusion: Psychological difficulties are more strongly associated with depressive symptoms than prosocial behavior. These findings highlight the importance of interventions that address both risk factors and strengths.